2015
DOI: 10.4174/astr.2015.89.4.176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-term outcomes and acute inflammatory response between laparoscopy-assisted and totally laparoscopic distal gastrectomy for early gastric cancer

Abstract: PurposeLaparoscopic gastrectomy is widely used to treat early gastric cancer. The advantages of totally laparoscopic distal gastrectomy (TLDG) are unproven, and some concerns remain regarding the early surgical outcomes due to its technical difficulty. We compared the early surgical outcomes and acute inflammatory response between patients undergoing TLDG and laparoscopy-assisted distal gastrectomy (LADG) for treatment of early gastric cancer.MethodsWe performed a retrospective study on 212 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Time to first flatus was 1.5 days. Median LOS was 5 days, and it was generally shorter than the results presented by other authors [3437]. In our opinion it is an effect of laparoscopy in combination with the ERAS protocol.…”
Section: Discussionsupporting
confidence: 40%
“…Time to first flatus was 1.5 days. Median LOS was 5 days, and it was generally shorter than the results presented by other authors [3437]. In our opinion it is an effect of laparoscopy in combination with the ERAS protocol.…”
Section: Discussionsupporting
confidence: 40%
“…Various therapeutic options are currently available for EGC, including endoscopic treatment, LG, and conventional open gastrectomy (3). LG has many advantages for patients with EGC, including good cosmesis, minimal postoperative pain, low operative stress, early postoperative recovery, early meal ingestion, a short postoperative hospital stay, and improved quality of life (17)(18)(19). The results of the present study indicate that LG for EGC is safe and feasible for elderly patients (9,20).…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, we identified that a postoperative change in the fibrinogen concentration > 20% was useful for predicting postoperative major complications following gynecologic laparoscopic surgeries. The role of acute-phase proteins in predicting the development of postoperative complications have been already investigated, but, to date, the majority of studies have focused on CRP [23][24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%